2020
DOI: 10.1182/bloodadvances.2019000770
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity C-reactive protein is associated with clonal hematopoiesis of indeterminate potential

Abstract: Clonal hematopoiesis of indeterminate potential (CHIP) is predictive of hematological cancers and cardiovascular diseases, but the etiology of CHIP initiation and clonal expansion is unknown. Several lines of evidence suggest that proinflammatory cytokines may favor mutated hematopoietic stem cell expansion. To investigate the potential link between inflammation and CHIP, we performed targeted deep sequencing of 11 genes previously implicated in CHIP in 1887 subjects aged >70 years from the Montreal Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 47 publications
(72 reference statements)
5
48
2
Order By: Relevance
“…Moreover, data (not yet peer-reviewed) by the same group [79] claim CHIP association with IL-6 and IL-β levels, but not with hs-CRP (in a wide analysis of 32 cohorts, with 97,691 individuals and identifying 4229 CHIP cases). On the contrary, a very recent study by Busque et al [80] shows that high-sensitivity (hs)-CRP is significantly higher in subjects with CHIP versus subjects without CHIP (analyzing, in total, 1887 subjects), supporting the hypothesis that a link between inflammation and CHIP-linked increased risk of CVD pathogenesis exists in ageing individuals. Despite these differences, taken together, these data confirm the association between inflammation, CHIP and aging.…”
Section: Chip the Chronic Inflammatory State And Ageing: One Culpritmentioning
confidence: 93%
“…Moreover, data (not yet peer-reviewed) by the same group [79] claim CHIP association with IL-6 and IL-β levels, but not with hs-CRP (in a wide analysis of 32 cohorts, with 97,691 individuals and identifying 4229 CHIP cases). On the contrary, a very recent study by Busque et al [80] shows that high-sensitivity (hs)-CRP is significantly higher in subjects with CHIP versus subjects without CHIP (analyzing, in total, 1887 subjects), supporting the hypothesis that a link between inflammation and CHIP-linked increased risk of CVD pathogenesis exists in ageing individuals. Despite these differences, taken together, these data confirm the association between inflammation, CHIP and aging.…”
Section: Chip the Chronic Inflammatory State And Ageing: One Culpritmentioning
confidence: 93%
“…Genomic DNA extracted from whole blood was studied by HTS of 36 genes recurrently mutated in myeloid malignancies. The studied panel included genes encoding proteins involved in kinase signaling (CALR (exon 9), CBL (exons 8-9), CSF3R (exons [14][15][16][17][18] (exons 1-11)), and NPM1 (exon 11). Notably, our panel did not include PPM1D, for which mutations have been frequently reported in CHIP, especially in patients treated for prior non-hematological cancer.…”
Section: Molecular Analysesmentioning
confidence: 99%
“…Case control studies have shown that CHIP was associated with a higher risk of hematological cancer [ 4 , 5 ], as expected, but also with an increase in incident coronary heart disease, ischemic stroke and all-cause mortality [ 4 , 9 , 10 ], and chronic obstructive pulmonary disease [ 6 , 7 ]. Interestingly, further studies have suggested a connection between cytokine-mediated processes and CHIP [ 6 , 9 , 11 , 12 , 13 , 14 ], with higher serum IL-6 [ 15 ] and C-reactive protein (CRP) [ 16 ] levels in CHIP carriers. Studies using murine models have also demonstrated that Dnmt3a- and Tet2 -deficient animals were characterized by impaired production of type I interferon and increased IL-6 production, respectively, compared to wild-type mice [ 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Somatic mutations in epigenetic regulatory genes such as DNMT3A and TET2 along with JAK2 V617F are among the most common CHIP mutations [8]. The presence of CHIP mutations is associated with inflammatory markers such as increased serum IL-6, TNF-α, IL-8 and high-sensitivity C-reactive protein (hsCRP) [12][13][14]. Compared to the incidence of CHIP in the general population from prior studies and published cohorts, the frequency of CHIP was higher in chronic inflammatory conditions such as aplastic anemia [15,16], ulcerative colitis patients [17] and in patients with aortic valve stenosis [18].…”
Section: Clonal Hematopoiesis Of Indeterminate Potential (Chip)mentioning
confidence: 99%